Preparedness of the entities for the IFRS for SMEs: an emerging country case - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2016)
Purpose - The purpose of this paper is to determine the preparedness of the small-and medium-sized enterprises (SMEs) for the International Financial Reporting Standard (IFRS) for SMEs in Turkey; and to analyze the effect of several firm characteristics on such preparedness. Design/methodology/approach - The preparedness of the SMEs was determined via a questionnaire survey. The effect of several characteristics of the SMEs (i.e. size, age, independent auditing, internationality, and the existence of an accounting department) on their preparedness was examined by employing non-parametric tests and logistic regression. Findings - This study found that the preparedness of the SMEs for IFRS for SMEs is low in Turkey. Several firm characteristics including, size, independent auditing, and internationality have a significant impact on the preparedness of the SMEs. Research limitations/implications - This study has some implications for several parties, including national and international standard setting authorities, entities, managers, and accounting professionals. SMEs are one of the most important actors in the adoption process of the IFRS for SMEs. Their preparedness level for IFRS for SMEs will present important clues to sustain an effective and successful adoption process. The results of this study show the profile of entities which are prepared for IFRS for SMEs that will be useful for standard authorities and regulatory bodies. The findings of this study will also be useful for other emerging countries' standard authorities because they will face similar problems in their adoption process. Originality/value - This research makes a significant contribution to the existing literature because there are only a few studies that analyze the preparedness for IFRS for SMEs, especially in emerging countries.
Keywords: Turkey; IFRS; Preparedness; Emerging markets; IFRS for SMEs; FINANCIAL-REPORTING STANDARDS; INTERNATIONAL ACCOUNTING STANDARDS; DISCLOSURE; AUSTRALIA; COMPANIES; RELEVANCE